Ketogenic diet and cancer treatment - Sousa, Daniel Donato de (2022)
Faced with an expressive increase in the last decades in the case of cancer in the world population, the need for a dietary strategy supporting conventional treatment for patients diagnosed with cancer has become evident, with the aim of obtaining positive results in the fight against the disease. This literature review study aimed to present the ketogenic diet (KD) as a nutritional intervention and its proposed mechanisms against cancer cells, as well as to characterize limitations in the literature currently available. The studies were selected from the BIREME, PUBMED, ScienceDirect databases, as well as books, institutional and government websites; using descriptors such as: ketogenic diet; chronic diseases; cancer; cancer treatment and oxidative stress; they were used in the English language. It has been proposed that, in the absence of blood glucose, cancer cells decrease their proliferation and enter a state of oxidative stress, as a consequence of a high-fat, carbohydrate-deficient diet, thus making them more sensitive to standardized treatments. such as radiation and chemotherapy. However, there is a need for further studies in humans in order to obtain better results and conclusions regarding this nutritional intervention.